Pemberdayaan Keluarga Melalui Usaha Kopi Keliling Di Cipinang Jakarta Timur - Muhammad Rizky Andi; Maida Alfita Lutfiana; Yunita Utami (Community Empowerment : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2024)
Of course, to encourage economic development in people's lives, there must be a sense of independence that arises from the community itself. Family is the smallest area in human life. Poverty is still a worrying problem in society, especially on poor households. Of course, strengthening poor families requires an increase in economic independence so that the resulting impact can last. This empowerment uses the Y-PAR method that allows students to actively build their knowledge by identifying, exploring, and addressing social issues through collaborative activities with poor families. This empowerment is a program from the Kemuhammadiyahan Course of Muhammadiyah Prof.Dr.Hamka University which is carried out in the Cipinang area, East Jakarta, and this empowerment is carried out for Mr. Mulyana's family as a partner in advancing economic independence. thanks to this empowerment, the family Mr. Mulyana started a traveling coffee business, making Mr. Mulyana's family financially independent